2016
DOI: 10.3310/hta20310
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fundus autofluorescence imaging for the diagnosis and monitoring of retinal conditions: a systematic review

Abstract: BackgroundNatural fluorescence in the eye may be increased or decreased by diseases that affect the retina. Imaging methods based on confocal scanning laser ophthalmoscopy (cSLO) can detect this ‘fundus autofluorescence’ (FAF) by illuminating the retina using a specific light ‘excitation wavelength’. FAF imaging could assist the diagnosis or monitoring of retinal conditions. However, the accuracy of the method for diagnosis or monitoring is unclear.ObjectiveTo conduct a systematic review to determine the accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
(360 reference statements)
0
6
0
Order By: Relevance
“…Instead, we re-ran our original MEDLINE search. 66 and supplemented this with a broad search in Google Scholar using the free text term 'fundus autofluorescence imaging'. The first 200 potentially relevant references identified in Google Scholar, as judged by one reviewer against the inclusion criteria, and all references identified in the MEDLINE search were imported into an Endnote library.…”
Section: Search Updatementioning
confidence: 99%
See 4 more Smart Citations
“…Instead, we re-ran our original MEDLINE search. 66 and supplemented this with a broad search in Google Scholar using the free text term 'fundus autofluorescence imaging'. The first 200 potentially relevant references identified in Google Scholar, as judged by one reviewer against the inclusion criteria, and all references identified in the MEDLINE search were imported into an Endnote library.…”
Section: Search Updatementioning
confidence: 99%
“…Full-text articles were screened by one reviewer and checked by a second reviewer. At both steps of the selection process, a standard study selection worksheet listing the inclusion criteria was employed, 66 and any disagreements were resolved by discussion among the two reviewers or, if necessary, by involving a third reviewer. If a study was reported in more than one article at the full-text assessment step, all the articles relating to the study were grouped together for the eligibility assessment.…”
Section: Selection Of Evidencementioning
confidence: 99%
See 3 more Smart Citations